Molecular imprinted polymers for separation science: A review of reviews. Issue 3 (26th December 2012) - Cheong, Won Jo; Yang, Song Hee; Ali, Faiz
<x xml:space="preserve">Abstract</x> Molecular imprinted polymer is an artificial receptor made by imprinting molecules of a template in a polymer matrix followed by removing the template molecules via thorough washing to give the permanent template grooves. They show favored affinity to the template molecule compared to other molecules, and this property is the basic driving force for such diverse application of this techniques. Such techniques have been increasingly employed in a wide scope of applications such as chromatography, sample pretreatment, purification, catalysts, sensors, and drug delivery, etc., mostly in bioanalytical areas. A major part of them is related to development of new stationary phases and their application in chromatography and sample pretreatment. Embodiments of molecular imprinted polymer materials have been carried out in a variety of forms such as irregularly ground particles, regular spherical particles, nanoparticles, monoliths in a stainless steel or capillary column, open tubular layers in capillaries, surface attached thin layers, membranes, and composites, etc. There have been numerous review articles on molecular imprinted polymer issues. In this special review, the reviews in recent ca. 10 years will be categorized into several subgroups according to specified topics in separation science, and each review in each subgroup will be introduced in the order of date with brief summaries and comments on new developments and different scopes of prospects. Brief summaries of each categories and conclusive future perspectives are also given.